IMPLEMENTATION OF INCLUSIVE EDUCATION MANAGEMENT IN IMPROVING EDUCATION QUALITY - Ikrom Shaliadi; Roiq Masyhudi Hamid (Molang: Journal Of Islamic Education, 2024)
This research focuses on implementing inclusive education management at SDN Lawangan Daya II Pamekasan. This study aims to explore the planning, implementation and evaluation of management to improve the quality of education. This research uses a qualitative approach of case study type. Data were collected through observation, documentation and interviews and analysed inductively. The main data sources were the principal, vice principal, teachers, student affairs and administration. The implementation of inclusive education management has had a significant impact on improving the quality of education. This impact can be seen through changes in student behaviour and increased academic achievement of students with special needs. This research provides insights into how inclusive education can be designed to meet the needs of all students and how an inclusive approach can help improve the quality of education for all students. It also shows how challenges in implementing inclusive education management can be overcome through synergistic cooperation between all relevant parties